Field emission studies of novel ZnO nanostructures in high and low field regions - Ramgir, Niranjan S.; Late, Dattatray J.; Bhise, Ashok B.; Mulla, Imtiaz S.; More, Mahendra A.; Joag, Dilip S.; Pillai, Vijayamohanan K. (Nanotechnology, 2006)
A study of the field emission characteristics of novel structures of ZnO, namely marigolds, multipods and microbelts, has been carried out in both the close proximity configuration and the conventional field emission microscope. The use of a conventional field emission microscope overcomes the drawback of arc formation at high field values. The nonlinearity in the Fowler - Nordheim ( F - N) plot, a characteristic feature of semiconductors has been observed and explained on the basis of electron emission from both the conduction and the valence bands. The current stability exhibited by these structures is also promising for future device applications.

Field emission investigations of RuO2-doped SnO2 wires - Bhise, Ashok B.; Late, Dattatray J.; Ramgir, Niranjan S.; More, Mahendra A.; Mulla, Imtiaz S.; Pillai, Vijayamohanan K.; Joag, Dilip S. (Applied Surface Science, 2007)
Field emission studies of a bunch and a single isolated RuO2:SnO2 wire have been performed. A current density of 5.73 x 10(4) A/cm(2) is drawn from the single wire emitter at an applied field of 8.46 x 10(4) V/mu m. Nonlinearity in the Fowler-Nordheim (F-N) plot has been observed and explained on the basis of electron emission from both the conduction and the valence bands of the semiconductor. The current stability recorded at the preset value of 1.5 LA is observed to be good. Overall the high emission current density, good stability and mechanically robust nature of the RuO2:SnO2 wires offer advantages as field emitters for many potential applications. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: doped semiconductor; field emission; field enhancement factor; RuO2; SnO2

Field emission investigation of single Fe-doped SnO2 wire - Bhise, Ashok B.; Late, Dattatray J.; Sathe, Bhaskar R.; More, Mahendra A.; Mulla, Imtiaz S.; Pillai, Vijayamohanan K.; Joag, Dilip S. (Solid State Sciences, 2009)
Tin oxide submicronwires doped with Fe element were prepared by the thermal evaporation method. Morphological and structural characterizations revealed wires with sub micron size and crystalline in nature. The field electron emission from the single Fe:SnO2 wire was carried out in conventional field emission microscope. The Fowler-Nordheim plot obtained from I-V characteristics of the wire showed a linear behavior typical that of metal. The field enhancement factor estimated from the slope of the F-N plot is 7455 cm(-1), indicating that the field emission is from nanometric features of the emitter. A current density of 10 A/cm(2) has been obtained at an applied field of 4.845 x 10(3) V/mu m. The field emission current-time record at a current level of 1 mu A for more than 3 h duration is promising for various field emissions based applications. (C) 2009 Published by Elsevier Masson SAS.
Keywords: Current stability; Fe doped; field emission; SnO2

Fabrication of In-doped SnO2 nanowire arrays and its field emission investigations - Bhise, Ashok B.; Late, Dattatray J.; Sathe, B.; More, Mahendra A.; Mulla, Imtiaz S.; Pillai, Vijayamohanan K.; Joag, Dilip S. (Journal of Experimental Nanoscience, 2010)
The field emission of In-doped SnO2 wire array has been performed in parallel plate diode configuration. A maximum current density of 60 mu A/cm2 is drawn from the emitter at an applied field of 4 V/mu m. The nonlinearity in the Fowler-Nordheim plot, characteristics of semiconductor emitter has been observed and explained on the basis of electron emission from both the conduction and the valence bands. The current stability recorded at a preset value of 1 mu A is observed to be good. The high emission current density, good current stability and mechanically robust nature of the wires offer unprecedented advantages as promising cold cathodes for many potential applications based on field emission.
Keywords: cold cathodes; device; Doping; field emission; Nanowires; SnO2

Fowler-nordheim plot behavior and mechanism of field electron emission from ZnO tetrapod structures - Al-Tabbakh, Ahmed A.; More, Mahendra A.; Joag, Dilip S.; Mulla, Imtiaz S.; Pillai, Vijayamohanan K. (ACS Nano, 2010)
Field emission measurements of current-voltage characteristics are reported for tetrapod structures of ZnO. The nonlinear Fowler-Nordheim (FN) plot is analyzed according to a model of calculation based on saturation of conduction band current and predominance of valence band current at high-field values. The simulated FN plot exhibits similar features to those observed experimentally. The model of calculation suggests that the slope variation of the FN plot, in the high-field and low-field regions, does not depend on the magnitude of saturation. Instead, it is a characteristic of the energy band structure and voltage-to-barrier-field conversion factor of the emitting material.
Keywords: field emission; Fowler-Nordheim plot; Nanostructures; nonlinearity; ZnO

Functionalization of SBA-15 mesoporous materials using ``thiol-ene click'' michael addition reaction - Kumari, Sushma; Malvi, Bharmana; Ganai, Anal Kumar; Pillai, Vijayamohanan K.; Sen Gupta, Sayam (Journal of Physical Chemistry C, 2011)
Methacrylate-labeled SBA-15 has been successfully synthesized from calcined SBA-15 and commercially available 3-trichlorosilyl propylmethacrylate. This material undergoes efficient thiol-ene ``click reaction'' with a variety of both thiol and disulfide-containing substrates in aqueous and organic media. The products were thoroughly characterized by a variety of analytical techniques including multinuclear (C-13, Si-29) solid-state NMR, TG-DTA, and nitrogen adsorption desorption studies. Disulfide-containing substrates in which the TCEP-mediated reduction of the disulfide bond and its subsequent addition to the methacrylate group anchored in SBA-15 in one-pot were used to synthesize a silica-protein hybrid material composed of biotin-labeled SBA-15 and streptavidin. Electrochemically active material was synthesized from the reaction of ferrocene-containing thiol and the methacrylate-labeled SBA-15. The ease of synthesis for the methacrylate-labeled SBA-15 material together with its ability to undergo efficient chemoselective thiol-ene reaction would make it a very attractive platform for the development of covalently anchored enzymes and sensors.

Fractional photo-current dependence of graphene quantum dots prepared from carbon nanotubes - Kundu, Sumana; Ghosh, Sujoy; Fralaide, Michael; Narayanan, T. N.; Pillai, Vijayamohanan K.; Talapatra, Saikat (Physical Chemistry Chemical Physics, 2015)
We report on the photo-conductivity studies of chemically synthesized graphene quantum dots (GQDs) of average size 12 nm obtained by the oxidative acid treatment of MWCNTs. The dependence of photocurrent I-ph (I-ph = I-ill - I-dark) on the laser intensity P under a wide range of laser intensities (5 mW <= P <= 60 mW) shows a fractional power dependence of I-ph on light intensity. The temperature dependence (300 K < T < 50 K) of I-ph observed in thin films of these GQDs indicates that in the higher temperature region (T > similar to 100 K), as the temperature increases, the number of thermally generated carriers increase resulting in increased I-ph. At sufficiently low temperatures (T <= 100 K), a constant I-ph is observed, indicating a constant photocarrier density. Such a behavior is typically observed in many photoactive disordered semiconductors, which are often used in a variety of applications. We believe that the investigations presented here will enhance our understanding of the photocurrent generation phenomenon in chemically obtained GQDs.

Facile green synthesis of BCN nanosheets as high-performance electrode material for electrochemical energy storage - Karbhal, Indrapal; Devarapalli, Rami Reddy; Debgupta, Joyashish; Pillai, Vijayamohanan K.; Ajayan, Pulickel M.; Shelke, Manjusha V. (Chemistry-A European Journal, 2016)
Two-dimensional hexagonal boron carbon nitride (BCN) nanosheets (NSs) were synthesized by new approach in which a mixture of glucose and an adduct of boric acid (H3BO3) and urea (NH2CONH2) is heated at 900 degrees C. The method is green, scalable and gives a high yield of BCN NSs with average size of about 1 mm and thickness of about 13 nm. Structural characterization of the as-synthesized material was carried out by several techniques, and its energy-storage properties were evaluated electrochemically. The material showed excellent capacitive behaviour with a specific capacitance as high as 244 F g(-1) at a current density of 1 A g(-1). The material retains up to 96% of its initial capacity after 3000 cycles at a current density of 5 A g(-1).
Keywords: boron; Doping; Electrochemistry; Nanoparticles; nitrides